Critical thinking : a concise guide - Bowell, Tracy, 1965-; Kemp, Gary, 1960 Oct. 15- (London ; New York : Routledge, 2010)
Critical thinking: a concise guide is a much-needed guide to argument analysis and a clear introduction to thinking clearly and rationally for oneself. Through precise and accessible discussion this book equips students with the essential skills required to tell a good argument from a bad one. This third edition has been revised and updated throughout, with new exercises, and up-to-date topical examples, including: "real-world" arguments; practical reasoning; understanding quantitative data, statistics, and the rhetoric used about them; scientific reasoning; and expanded discussion of conditionals, ambiguity, vagueness, slippery slope arguments, and arguments by analogy.
Preface to the first edition -- Preface to the second edition -- Preface to the third edition -- Introduction and preview -- Introducing arguments -- Linguistic phenomena and rhetorical ploys -- Logic: deductive validity -- Logic: inductive force -- The practice of argument-reconstruction -- Issues in argument assessment -- Pseudo-reasoning -- Truth knowledge and belief.
Includes glossary.
Includes bibliographical references and index.
Keywords: Critical thinking; Critical thinking -- Study and teaching; Language and logic; Reasoning